PENGOLAHAN LIMBAH UNTUK PERABOT INTERIOR RUMAH TINGGAL PONDOK PESANTREN AR ROUDHLOH NGRINGO PALUR KARANGANYAR - Sukirno Sukirno; Sunarmi Sunarmi (Institut Seni Indonesia Surakarta, 2020)
This activity aims to give training and accompanying on interior ordering by using waste cardboard. The activity is implemented based on the phenomena in the pondok (Muslim boarding school) showing that there is the same problem that is limitedness of room and furniture so that the bedroom is not conducive for studying. The activity will be executed in Pondok Pesantren Ar Roudhloh Ngringo Palur Karanganyar. The strategy used is the approach of demonstration and appreciation while the method used is speech, discussion, and direct practice. The application of the demonstration and appreciation method is hoped to be able to practice and give appreciation. Partner can directly practice in accordance to his capacity and also measure or give appreciation towards his own work as well as another work in his group maximally so that the services team can train and accompany them suitable to their needs in the field. The result covers: the activity has a positive impact, it can be seen from the rooms that change from the dirty rooms to the clean and tidy rooms even with the simple furniture. The main target of usage cardboard waste extends to the board of building waste which has been available in the Pondok. The success needs for about two months duration. At the beginning, santri (learners at Pondok) is not interested in the activity but finally they show the positive reaction.Keywords: motivation, cardboard furniture, appreciation.